Let’s TikTok to learn to speak English - Ahmad Tarmizi, Siti Amirah; Hassan, Ariezal Afzan; Mahmud, Najihah; Mohamed, Amaal Fadhlini; Ghazali, Linira; Kaur Gill, Kavarljit; Abdullah, Arifuddin (Academica Press Solutions, 2023)
The spread of English as the world language has resulted in the need for people in many countries to be well-versed in that language and this includes Malaysia. While there have been many efforts to enhance English oral communication skills among Malaysian learners at all educational levels, their English performance in recent years remains unsatisfactory. Thus, inspired by Dwight Atkinson’s sociocognitive theory which views human mind, body, and socially mediated world as integrally intertwined in a rich and complex system of L2 learning, this study suggests that the social media TikTok can become an effective tool to mediate learners’ cognitive activities while learning to speak in English. The capacity of TikTok to provide a wide range of resources can become great scaffolding to accommodate the different needs of the learners. This can provide alternative pedagogical practices to improve oral communication skills among Malaysian learners.